Pengelolaan Program Parenting di TK IT X Kecamatan Ibun - Wilin Irania (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Parenting services are an integral part of the PAUD program, which involves parents and the community. There are various kinds of problems faced by PAUD institutions in implementing parenting programs starting from preparation, implementation, and evaluation. This study aims to describe: (1) preparation (2) implementation (3) and evaluation of the parenting program in Kindergarten IT Mutiara Embun Pagi (4) as well as the results of the parenting program felt by parents of students at Kindergarten IT Mutiara Embun Pagi. This study uses a descriptive method with a qualitative approach that aims to describe an incident during the research process at Kindergarten IT Mutiara Embun Pagi. Primary data sources are principals, teachers, and parents of the Kindergarten IT Mutiara Embun Pagi. Qualitative interview data collection techniques (Qualitative Interview), Qualitative Audio and Visual Materials (Qualitative audio and visual materials), Qualitative Observations (Qualitative observations). Data analysis was carried out in stages, namely (1) data reduction, (2) data presentation, (3) conclusion drawing and verification. The validity of the data through credibility (Triangulation or triangulation and Referencial Adequacy Checks) transferability , dependability , and confirmability. The results showed that: (1) Of the 6 activities in the preparation stage of the parenting program, only 2 activities were carried out in TK IT X (2) Of the 5 forms of implementation of the parenting program , only 1 was not implemented in Kindergarten IT Mutiara Embun Pagi, namely a visit to home, (3) Of the 3 forms of evaluation, only 2 methods were used in evaluation activities, (4) parents felt the benefits of the parenting program, namely increasing parental insight regarding parenting so that they changed parenting patterns at home. Abstrak. Layanan parenting menjadi salah satu program yang tidak terpisahkan dari program PAUD, yang mana melibatkan orang tua dan masyarakat. Terdapat berbagai macam persoalan yang dihadapi lembaga PAUD dalam melaksanakan program parenting mulai dari persiapan, pelaksanaan, dan evaluasi. Penelitian ini bertujuan menggambarkan: (1) persiapan (2) pelaksanaan (3) dan evaluasi program parenting di TK IT X (4) serta hasil program parenting yang di rasakan oleh orang tua siswa di TK IT X. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif yang bertujuan menggambarkan suatu kejadian selama terjadinya proses penelitian di TK IT X. Sumber data primer adalah kepala sekolah, guru, dan orang tua murid di TK IT X. Teknik pengumpulan data wawancara kualitatif (Qualitatif Interview), Meteri Audio dan Visual Kualitatif (Qualitatif audio and visual materials), Observasi Kualitatif (Qualitatif Observation). Pengelolaan data dilakukan secara bertahap yaitu (1) Reduksi data, (2) Penyajian data (3) Penarikan simpulan dan verifikasi. Keabsahan data melalui credibility (Triangulation atau triangulasi dan Referencial Adequacy Checks) transferability, dependability, dan confirmability. Hasil penelitian menunjukkan bahwa: (1) Dari 6 kegiatan pada tahap persiapan program parenting hanya 2 kegiatan yang terlaksana di TK IT X (2) Dari 5 bentuk pelaksanaan program parenting hanya 1 yang tidak terlaksana di TK IT X yaitu kungjungan ke rumah, (3) Dari 3 bentuk evaluasi hanya 2 metode yang digunakan dalam kegiatan evaluasi, (4) orang tua merasakan manfaat adanya program parenting yaitu bertambahnya wawasan orang tua terkait parenting sehingga mengubah pola asuh di rumah.